Design and Formulation of Hybrid Bioactive Coatings Using Thermal Spray Process - Singh, Harpreet (My University, 2010)
Hydroxyapatite Ca10(PO4)6(OH)2, commonly referred to as HA, has attracted wide spread interest from both the orthopaedic and dental fields due to its excellent biocompatibility and tissue bioactivity properties. Hydroxyapatite is chemically similar to the mineral component of bones and hard tissues in mammals. It is one of the few materials that are considered bioactive, meaning that it will support bone growth when used in orthopaedic and dental applications. Despite excellent properties as a biomaterial, the ceramic nature and the inherent mechanical properties of HA specifically brittleness, poor tensile strength and poor impact resistance have restricted its application in many load-bearing applications. In order for the HA coating to be effective and reliable, it must be strongly bonded to the metallic surface. Substitution of other elements has shown the potential to improve the bioactivity of HA. Titanium oxide (TiO2) and Aluminium oxide (Al2O3) are added in HA powder to prevent corrosion and wear of metallic surface. In the present investigation, an attempt is made to develop HA powder from Chicken eggshell, a natural apatite rich substance through heat treatment method. Eggshell, a cheaper source of HA is generated as waste material during egg processing. Fourier transform-infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) techniques are employed to investigate the proof of formation of HA phase. The blood clotting test shows that both the powders are efficient and compatible with human blood. The coating of Hybrid powder using HA, TiO2, Al2O3 is developed on SS 304L metal substrate by using detonation gun spray technique. Coated samples are obtained at various D-Gun parameters. Samples are tested for Wear, Micro structural analysis, Hardness, Micro hardness, etc., to find the optimum D-Gun parameters.
ME
Keywords: Bioactive coatings; thermal spray process; detonation spray process; hydroxyapatite; stainless steel; wear resistance; corrosion resistance; biomedical implants